Experimental and numerical studies to assess the energy performance of naturally ventilated PV façade systems. (1st May 2017) - Shahrestani, Mehdi; Yao, Runming; Essah, Emmanuel; Shao, Li; Oliveira, Armando C.; Hepbasli, Arif; Biyik, Emrah; Caño, Teodosio del; Rico, Elena; Lechón, Juan Luis
Highlights: Study the influence of ventilation effect on PV façades. Analyse energy performance of PV façade systems based on experimental data. Develop a numerical model for ventilated PV facades. Evaluate the numerical model using experimental data. Abstract: This paper presents a holistic approach to assess the energy performance of a naturally ventilated PV façade system. A rigorous combined experimental and numerical approach is established. The real energy performance of the system has been evaluated through a long-term high resolution monitoring of a typical ventilated PV façade system. A numerical model based on TRaNsient SYstem Simulation (TRNSYS) package was developed to assess the thermal and energy performance of the system, which has been verified by a series of statistical analysis using the data collected from the experiment. The validated model was then used to assess the energy and thermal performance of a 7.4 kWp prototype ventilated PV façade system in Izmir, Turkey. The results of this study demonstrated that ventilation in the air cavity of the PV façade system could significantly improve energy performance of the system even in a southeast facing façades. The quantitative analysis provides useful guidance to the system designers for the improvement of energy efficiency of the PV facade system.